Dyslipidemia and tobacco smoking synergistically increase serum manganese - Rivera-Mancía, Susana; Colín-Ramírez, Eloisa; Montes, Sergio; Cartas-Rosado, Raúl; Vargas-Barrón, Jesús; Vallejo, Maite (Investigación Clínica, 2017)
Ver Resumen PDF.